2015
DOI: 10.1016/j.celrep.2015.11.048
|View full text |Cite|
|
Sign up to set email alerts
|

Quantification of Protein Levels in Single Living Cells

Abstract: Accurate measurement of the amount of specific protein a cell produces is important for investigating basic molecular processes. We have developed a technique that allows for quantitation of protein levels in single cells in vivo. This protein quantitation ratioing (PQR) technique uses a genetic tag that produces a stoichiometric ratio of a fluorescent protein reporter and the protein of interest during protein translation. The fluorescence intensity is proportional to the number of molecules produced of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
71
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 82 publications
(75 citation statements)
references
References 39 publications
0
71
0
Order By: Relevance
“…RPL13a is expressed in all eukaryotic cells at consistent levels, and is routinely used as a reference housekeeping gene for normalization of quantitative mRNA and protein measurements [14,15,16]. The quantification of RPL13a by the insertion of a PQRGFP nols reporter at the end of its coding sequence (Figure 2A) can therefore be used as a measure of a cell's individual transcriptional and translational status [5]. …”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…RPL13a is expressed in all eukaryotic cells at consistent levels, and is routinely used as a reference housekeeping gene for normalization of quantitative mRNA and protein measurements [14,15,16]. The quantification of RPL13a by the insertion of a PQRGFP nols reporter at the end of its coding sequence (Figure 2A) can therefore be used as a measure of a cell's individual transcriptional and translational status [5]. …”
Section: Methodsmentioning
confidence: 99%
“…For example, we used single-cell protein and mRNA quantification in single cells from human and mouse to determine the covariation between mRNA expression and protein amounts. We found that mRNA expression is a weak predictor of protein translation [5]. Recently, simultaneous measurement of RNA and protein was also performed in single cells using microfluidics, and a high heterogeneity and poor mRNA-to-protein correlations were also observed [9,10,11].…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations